Impaired implicit learning of syntactic structure in children with developmental language disorder: Evidence from syntactic priming. (June 2018) - Garraffa, Maria; Coco, Moreno I; Branigan, Holly P
Background and aims: Implicit learning mechanisms associated with detecting structural regularities have been proposed to underlie both the long-term acquisition of linguistic structure and a short-term tendency to repeat linguistic structure across sentences (structural priming) in typically developing children. Recent research has suggested that a deficit in such mechanisms may explain the inconsistent trajectory of language learning displayed by children with Developmental Learning Disorder. We used a structural priming paradigm to investigate whether a group of children with Developmental Learning Disorder showed impaired implicit learning of syntax (syntactic priming) following individual syntactic experiences, and the time course of any such effects. Methods: Five- to six-year-old Italian-speaking children with Developmental Learning Disorder and typically developing age-matched and language-matched controls played a picture-description-matching game with an experimenter. The experimenter's descriptions were systematically manipulated so that children were exposed to both active and passive structures, in a randomized order. We investigated whether children's descriptions used the same abstract syntax (active or passive) as the experimenter had used on an immediately preceding turn (no-delay) or three turns earlier (delay). We further examined whether children's syntactic production changed with increasing experience of passives within the experiment. Results: Children with Developmental Learning Disorder's syntactic production was influenced by the syntax of the experimenter's descriptions in the same way as typically developing language-matched children, but showed a different pattern from typically developing age-matched children. Children with Developmental Learning Disorder were more likely to produce passive syntax immediately after hearing a passive sentence than an active sentence, but this tendency was smaller than in typically developing age-matched children. After two intervening sentences, children with Developmental Learning Disorder no longer showed a significant syntactic priming effect, whereas typically developing age-matched children did. None of the groups showed a significant effect of cumulative syntactic experience. Conclusions: Children with Developmental Learning Disorder show a pattern of syntactic priming effects that is consistent with an impairment in implicit learning mechanisms that are associated with the detection and extraction of abstract structural regularities in linguistic input. Results suggest that this impairment involves reduced initial learning from each syntactic experience, rather than atypically rapid decay following intact initial learning. Implications: Children with Developmental Learning Disorder may learn less from each linguistic experience than typically developing children, and so require more input to achieve the same learning outcome with respect to syntax. Structural priming is an effective technique for manipulating both input quality and quantity to determine precisely how Developmental Learning Disorder is related to language input, and to investigate how input tailored to take into account the cognitive profile of this population can be optimised in designing interventions.